Modeling of post-traumatic epilepsy and experimental research aimed at its prevention - Mosini, A.C. (Braz J Med Biol Res, 2020)
Research on the prevention of post-traumatic epilepsy (PTE) has seen remarkable advances regarding its physiopathology in recent years. From the search for biomarkers that might be used to indicate individual susceptibility to the development of new animal models and the investigation of new drugs, a great deal of knowledge has been amassed. Various groups have concentrated efforts in generating new animal models of traumatic brain injury (TBI) in an attempt to provide the means to further produce knowledge on the subject. Here we forward the hypothesis that restricting the search of biomarkers and of new drugs to prevent PTE by using only a limited set of TBI models might hamper the understanding of this relevant and yet not preventable medical condition.